'Poking the skunk': Ethical and medico‐legal concerns in research about patients' experiences of medical injury. (20th June 2019) - Schulz Moore, Jennifer; Mello, Michelle M.; Bismark, Marie
Abstract: Improving how health care providers respond to medical injury requires an understanding of patients' experiences. Although many injured patients strongly desire to be heard, research rarely involves them. Institutional review boards worry about harming participants by asking them to revisit traumatic events, and hospital staff worry about provoking lawsuits. Institutions' reluctance to approve this type of research has slowed progress toward responses to injuries that are better able to meet patients' needs. In 2015–2016, we were able to surmount these challenges and interview 92 injured patients and families in the USA and New Zealand. This article explores whether the ethical and medico‐legal concerns are, in fact, well‐founded. Consistent with research about trauma‐research‐related distress, our participants' accounts indicate that the pervasive fears about retraumatization are unfounded. Our experience also suggests that because being heard is an important (but often unmet) need for injured patients, talking provides psychological benefits and may decrease rather than increase the impetus to sue. Our article makes recommendations to institutional review boards and researchers. The benefits to responsibly conducted research with injured patients outweigh the risks to participants and institutions.